1995
DOI: 10.3928/0098-9134-19951101-04
|View full text |Cite
|
Sign up to set email alerts
|

WHEN CARING LEAVES BRUISES: The Effects of Staff Education on Resident Aggression

Abstract: 1. Physical aggression toward nursing staff by confused elderly residents is a very common and frustrating clinical nursing problem in long-term care facilities. 2. Some physical aggression may be associated with a lack of knowledge about dementia, therefore staff inservice education may be one way of reducing some forms of physical aggression. 3. The authors found a 50% reduction in reported physical aggression from elderly residents after a staff education program on dementia and aggression was implemented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
85
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(88 citation statements)
references
References 12 publications
3
85
0
Order By: Relevance
“…Working in a nursing home or long-term care facility is associated with a high risk of experiencing aggression [3].Studies show that aggressive behavior is more likely to occur among older people with cognitive impairment than among those with no cognitive impairment [2,4,5] although cognitively intact residents also threaten or assault the caregivers [6]. Irrespective of whether demented residents can be held responsible for their aggressive behavior, many gerontological nurses find that physical or verbal attacks by an elderly person they are giving nursing care to is one of the most difficult, emotionally distressing, and potentially dangerous aspects of their work [7], often resulting in feelings of powerlessness, sadness, anger, and ineffectiveness [8].Some studies have investigated the prevalence of aggression and associated factors in nursing homes, but it is probable that nursing home residents' aggressive behavior often goes underreported in both prevalence measures and nursing documentation. Possible causes for underreporting are a lack of competence to cope with aggressive behavior, feelings of failure, or the assumption that aggressive behavior is a common feature in the care of the elderly, especially those with psychological disturbance [1,4,9,10].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Working in a nursing home or long-term care facility is associated with a high risk of experiencing aggression [3].Studies show that aggressive behavior is more likely to occur among older people with cognitive impairment than among those with no cognitive impairment [2,4,5] although cognitively intact residents also threaten or assault the caregivers [6]. Irrespective of whether demented residents can be held responsible for their aggressive behavior, many gerontological nurses find that physical or verbal attacks by an elderly person they are giving nursing care to is one of the most difficult, emotionally distressing, and potentially dangerous aspects of their work [7], often resulting in feelings of powerlessness, sadness, anger, and ineffectiveness [8].Some studies have investigated the prevalence of aggression and associated factors in nursing homes, but it is probable that nursing home residents' aggressive behavior often goes underreported in both prevalence measures and nursing documentation. Possible causes for underreporting are a lack of competence to cope with aggressive behavior, feelings of failure, or the assumption that aggressive behavior is a common feature in the care of the elderly, especially those with psychological disturbance [1,4,9,10].…”
mentioning
confidence: 99%
“…Working in a nursing home or long-term care facility is associated with a high risk of experiencing aggression [3].Studies show that aggressive behavior is more likely to occur among older people with cognitive impairment than among those with no cognitive impairment [2,4,5] although cognitively intact residents also threaten or assault the caregivers [6]. Irrespective of whether demented residents can be held responsible for their aggressive behavior, many gerontological nurses find that physical or verbal attacks by an elderly person they are giving nursing care to is one of the most difficult, emotionally distressing, and potentially dangerous aspects of their work [7], often resulting in feelings of powerlessness, sadness, anger, and ineffectiveness [8].…”
mentioning
confidence: 99%
“…[12,13] Nursing home staff report that aggression is the most distressing behavior in PWDs, and approximately 50% of nursing assistants report being injured because of aggressive behavior. [14,15] Caregivers who experience aggression from a PWD report higher caregiver burden, experience worse physical functioning, and have higher pain scores. [13] In turn, this can lead to staff burnout and high turnover rates, which will likely reduce the quality of care and increase the cost of care.…”
Section: Prevalence Of Aggression In Pwdsmentioning
confidence: 99%
“…Prior to 2007, four studies found that training programs for nursing staff were effective. [14,[49][50][51] More recently, three staff intervention studies found significant reductions in aggression. [39][40][41] These programs tend to involve multiple sessions and teach specific skills such as identifying and modifying environmental precipitants of aggression, communication techniques, learning to view problem behaviors as an expression of an unmet need, learning to examine antecedents to aggressive behaviors and their consequences, and distraction.…”
Section: Summary Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation